Daur Ulang Limbah Kertas Menjadi Karton Gembos dan Kelayakan Usahanya - Siti Qorrotu Aini; Jatmiko Wahyudi; Aeda Ernawati; Arieyanti Dwi Astuti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Pati regency has the potential to establish a business in paper waste recycling. Paper waste can be recycled into a high added-value product called paperboard. This study provides information about the production process of paperboard from paper waste as well as its economic and environmental benefits. Last, the feasibility of the establishment a company that recycles paper waste into paperboard is analyzed. The research method uses both qualitative and quantitative methods. The results showed that there are several steps in making paperboard from paper waste including raw materials preparation, pulping, printing, cutting, and packaging. Environmentally, the company will recycle 192 tons/year of paper waste and 30 tons/year of sludge. Economically, the company will give benefits by providing job opportunities, generating tax for the government, and generating income. This company is feasible to establish based three feasibility indicators namely payback period, net present value (NPV), and internal return rate(IRR). Payback period is 2 years 8 months; NPV is Rp.880,877,817 (above 0) and IRR is 25.07% (above the interest rate).